PREDIKAT KEDUA DALAM BAHASA INDONESIA - I Nyoman Kardana (Program Magister Linguistik Universitas Udayana, 2010)
This study is related with secondary predicate in Indonesian language. Data was colleted from speakers of Indonesian and from daily newspaper Bali Post as well. Data was collected by applying observation method with its various techniques. Himmelmann and Schultze (2005) say that there are four types of secondary predicate, namely (1) depictive, (2) resultative, (3) circumstantial, and (4) predicative complement. Based on the analysis it was found that the four types of secondary predicate are also found in Indonesian language. Depictive can be classified into depictive secondary predicates modifying subject and those that modify object. Seen from word category, the secondary predicate in Indonesian language can be filled in by adjective for depictive, resultative, and circumstantial, and noun for predicative complement. The existence of the adjectives in secondary predicate of depictive, resultative, and circumstantial are optional, but the noun in secondary predicate of predicative complement is obligatory.